Accuracy Tests of Serum Vitamin D and Calcium Levels in Chorioamnionitis: Uji Kesesuaian Kadar Serum Vitamin D dan Kalsium pada Korioamnionitis - Muhammad F. C. Husna; Peby M. Lestari; Ahmad K. Syamsuri; Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: To compare the sensitivity and specificity of the diagnosis of chorioamnionitis in preterm labor using serum vitamin D and calcium in Dr.Mohammad Hoesin Hospital Palembang.Method: This diagnostic test was carried out in the Obstetrics and Gynecology Department of Dr. Mohammad Hoesin Hospital Palembang from October 2018 to April 2019. Research subjects were women in preterm labor with chorioamnionitis. We collected 39 samples and 36 of them met the inclusion criteria.Results: Eighteen patients with hypovitaminosis vitamin D had chorioamnionitis with a sensitivity value of 94.74%, specificity 5, 88%, positive predictive value (PPV) 52.9% and negative predictive value (NPV) 50%. Two of the 4 patients with hypocalcemia had chorioamnionitis with sensitivity of 10.53%, specificity 88. 24%, positive predictive value (PPV) 50% and negative predictive value (NPV) 46. 9%.Conclusion: Reliability of diagnosis accuracy of serum vitamin and calcium levels against chorioamnionitis is poor.Keywords: accuracy tests, calcium, chorioamnionitis, vitamin D Abstrak Tujuan: Membandingkan sensitivitas dan spesifisitas diagnosis korioamnionitis pada partus prematurus antara serum vitamin D dan kalsium di Rumah Sakit Dr. Mohammad Hoesin Palembang.Metode: Uji diagnostik dilakukan di Departemen Obstetrik dan Ginekologi RSUP Dr. Mohammad Hoesin Palembang. Penelitian dilaksanakan sejak Oktober 2018 hingga April 2019. Subjek penelitian adalah wanita hamil prematur yang didiagnosa korioamnionitis. Terdapat 39 sampel dimana 36 sampel termasuk kriteria inklusi.Hasil: Terdapat 18 pasien dengan hipovitaminosis vitamin D memiliki luaran koriaoamnionitis memiliki nilai sensitivitas 94,74%, spesifisitas 5, 88%, positive predictive value (PPV) 52, 9% dan negative predictive value (NPV) 50%. 2 dari 4 pasien dengan hipokalsemia memiliki luaran korioamnionitis memiliki sensitivitas 10, 53%, spesifisitas 88, 24%, positive predictive value (PPV) 50% dan negative predictive value (NPV) 46, 9%.Kesimpulan: Akurasi diagnosis kadar serum vitamin dan kalsium terhadap luaran korioamnionitis memiliki derajat kesesuaian (realiabilitas) kurang baik.Kata kunci: kalsium, korioamnionitis, uji kesesuaian, vitamin D